HIV treatment as prevention: the key to an AIDS-free generation - Hull, Mark W. (2013)
The presence of elevated HIV viral load within blood and genital secretions is a critical driver of transmission events. Long-term suppression of viral load to undetectable levels through the use of antiretroviral therapy is now standard practice for clinical management of HIV. Antiretroviral therapy therefore can play a key role as a means to curb HIV transmission. Results of a randomized clinical trial, in conjunction with several observational studies, have now confirmed that antiretroviral therapy markedly decreases HIV transmission risk. Mathematical models and population-based ecologic studies suggest that further expansion of antiretroviral coverage within current guidelines can play a major role in controlling the spread of HIV. Expansion of so-called “Treatment as Prevention” initiatives relies upon maximal uptake of the HIV continuum-of-care cascade to allow for successful identification of those not yet known to be HIV-infected, engagement of patients in appropriate care, and subsequently achieving sustained virologic suppression in patients with the use of antiretroviral therapy. Since 2010, the Joint United Nations AIDS (UNAIDS) program has called for the inclusion of antiretroviral treatment as a key pillar in the global strategy to control the spread of HIV infection. This has now been invigorated by the release of the World Health Organization’s 2013 Consolidated Antiretroviral Therapy Guidelines, recommending treatment to be offered to all HIV-infected individuals with CD4 cell counts below 500/mm(3), and, regardless of CD4 cell count, to serodiscordant couples, TB and HBV co-infected individuals, pregnant women, and children below the age of 5 years.